Progress on the development of key technologies for the fourth generation ECR ion source FECR. Issue 1 (1st April 2022) - Sun, L; Lu, W.; Zhao, H.W.; Guo, J. W.; Wu, W.; Wu, B. M.; Ou, X.J.; Mei, E. M.; Zheng, S.J.; Zhang, X. Z.; Li, L.B.; Zhu, L.; et al.
Abstract: A 4 th generation ECR (Electron Cyclotron Resonance) ion source FECR (First 4 th generation ECR ion source) is under development at IMP. Aiming to be operated with the microwave power of 20 kW at 45 GHz, FECR is equipped with a fully superconducting Nb3Sn magnet and conventional parts durable for high power ECR plasma heating and optimum for intense beam production and extraction. Breakthroughs on the Nb3Sn superconducting magnet, high power density plasma chamber, high temperature oven, and so on have been successfully demonstrated recently. The prototype Nb3Sn cold mass has been successfully tested. The plasma chamber with an innovative structure of micro-channel cooling structure has been tested which enables SECRAL-II ion source operated continuously for more than 1, 100 hours with ∼300 eμA Kr 26 + for routine operation at the microwave power level of ∼5 kW. A high temperature inductive heating oven has also been developed and used for intense uranium beam production. This talk will present the recent progress on the development of key technologies for the 4th generation ECR ion source.